Creating the American junkie : addiction research in the classic era of narcotic control - Acker, Caroline Jean, 1947- (Baltimore : Johns Hopkins University Press, 2002)
"Heroin was only one drug among many that worried Progressive Era anti-vice reformers, but by the mid-twentieth century, heroin addiction came to symbolize irredeemable deviance. Creating the American Junkie examines how psychiatrists and psychologists produccd a construction of opiate addicts as deviants with inherently flawed personalities who were caught in the grip of a dependency from which few would eacape. Their portrayal of the tough urban addict helped bolster the federal government's policy of drug prohibition and created a social context that made the life of the American heroin addict - or junkie - more, not less, precarious in the wake of Progressive Era reforms."--Jacket.
Heroin addiction and urban vice reform -- The opportunistic approach -- The technological fix : the search for a nonaddicting analgesic -- Constructing the addict career -- The junkie as psychopath -- Healing vision and bureaucratic reality -- The addict in the social body.
Includes bibliographical references and index.
Print version record.
Keywords: Heroin abuse -- Social aspects -- United States; Heroin abuse -- Research -- United States; Drug addiction -- Research -- United States; Drug addicts -- Research -- United States; Drug addicts -- Government policy -- United States; Heroin Dependence -- history; Drug and Narcotic Control -- history; Heroin Dependence -- etiology; Research -- history; United States; Héroïnomanie -- Aspect social -- États-Unis.; Héroïnomanie -- Recherche -- États-Unis.; Toxicomanie -- Recherche -- États-Unis.; Toxicomanes -- Recherche -- États-Unis.; Toxicomanes -- Politique gouvernementale -- États-Unis.; SELF-HELP -- Substance Abuse & Addictions -- Drug Dependence; Drug addiction -- Research; Drug addicts -- Government policy; Drug addicts -- Research; Heroin abuse -- Research; Heroin abuse -- Social aspects; United States; Drogenabhängigkeit; Persönlichkeitskonstrukt; Wissenschaftstheorie; Gesellschaft; Drugsverslaving; Onderzoek; Overheidsbeleid; Geschichte 1900-1945.; USA; Electronic books; Electronic books